Convergence of Scaffold-Guided Bone Reconstruction and Surgical Vascularization Strategies—A Quest for Regenerative Matching Axial Vascularization - Sparks, David S.; Savi, Flavia Medeiros; Saifzadeh, Siamak; Schuetz, Michael A.; Wagels, Michael; Hutmacher, Dietmar W. (Frontiers in Bioengineering and Biotechnology, 2020)
The prevalent challenge facing tissue engineering today is the lack of adequate vascularization to support the growth, function, and viability of tissue engineered constructs (TECs) that require blood vessel supply. The research and clinical community rely on the increasing knowledge of angiogenic and vasculogenic processes to stimulate a clinically-relevant vascular network formation within TECs. The regenerative matching axial vascularisation approach presented in this manuscript incorporates the advantages of flap-based techniques for neo-vascularisation yet also harnesses the in vivo bioreactor principle in a more directed “like for like” approach to further assist regeneration of the specific tissue type that is lost, such as a corticoperiosteal flap in critical sized bone defect reconstruction.